Epigenetic effects of metformin: From molecular mechanisms to clinical implications - Bridgeman, S.; Ellison, G.; Melton, Phillip; Newsholme, Philip; Mamotte, Cyril (2018)
There is a growing body of evidence that links epigenetic modifications to type 2 diabetes. Researchers have more recently investigated effects of commonly used medications, including those prescribed for diabetes, on epigenetic processes. This work reviews the influence of the widely used antidiabetic drug metformin on epigenomics, microRNA levels and subsequent gene expression, and potential clinical implications. Metformin may influence the activity of numerous epigenetic modifying enzymes, mostly by modulating the activation of AMP-activated protein kinase (AMPK). Activated AMPK can phosphorylate numerous substrates, including epigenetic enzymes such as histone acetyltransferases (HATs), class II histone deacetylases (HDACs) and DNA methyltransferases (DNMTs), usually resulting in their inhibition; however, HAT1 activity may be increased. Metformin has also been reported to decrease expression of multiple histone methyltransferases, to increase the activity of the class III HDAC SIRT1 and to decrease the influence of DNMT inhibitors. There is evidence that these alterations influence the epigenome and gene expression, and may contribute to the antidiabetic properties of metformin and, potentially, may protect against cancer, cardiovascular disease, cognitive decline and aging. The expression levels of numerous microRNAs are also reportedly influenced by metformin treatment and may confer antidiabetic and anticancer activities. However, as the reported effects of metformin on epigenetic enzymes act to both increase and decrease histone acetylation, histone and DNA methylation, and gene expression, a significant degree of uncertainty exists concerning the overall effect of metformin on the epigenome, on gene expression, and on the subsequent effect on the health of metformin users.